2017
DOI: 10.1002/ejoc.201701005
|View full text |Cite
|
Sign up to set email alerts
|

The Manganese‐Catalyzed Cross‐Coupling Reaction and the Influence of Trace Metals

Abstract: The substrate scope of the MnCl2‐catalyzed cross‐coupling between aryl halides and Grignard reagents has been extended to several methyl‐substituted aryl iodides by performing the reaction at elevated temperature in a microwave oven. A radical clock experiment revealed the presence of an aryl radical as an intermediate leading to the proposal of an SRN1 pathway for the coupling. The mechanistic information gave rise to suspicion about two previously published cross‐coupling reactions catalyzed by manganese(II)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 39 publications
4
21
0
Order By: Relevance
“…Essentially no imine was formed when the reaction was conducted in the absence of complex 2 . The possibility for trace metal impurities is a serious concern in the development of reactions with new metal catalysts18 and studies have shown that some coupling reactions with manganese catalysts are most likely mediated by traces of other elements 19. For that reason, complex 2 was analyzed by inductively coupled plasma mass spectrometry (ICP-MS) for traces of other metals known to perform alcohol dehydrogenations.…”
Section: Resultsmentioning
confidence: 99%
“…Essentially no imine was formed when the reaction was conducted in the absence of complex 2 . The possibility for trace metal impurities is a serious concern in the development of reactions with new metal catalysts18 and studies have shown that some coupling reactions with manganese catalysts are most likely mediated by traces of other elements 19. For that reason, complex 2 was analyzed by inductively coupled plasma mass spectrometry (ICP-MS) for traces of other metals known to perform alcohol dehydrogenations.…”
Section: Resultsmentioning
confidence: 99%
“…This mild and moisture compatible Lewis acid has been found to promote a handful of relevant transformations, such as mesylate to chloride conversion [44], esterification and transesterification reactions [45,46], Michael addition [47], glucose to fructose isomerization [48], condensation of carbonyls with amine derivatives [49], carbonyl reduction [50] and the reductive amination of ketones [51]. The salt has also been employed as a catalyst for cross couplings leading to C-X (X=N, S) [52,53] or C-C bond formation [54,55], and in C-H activation reactions resulting in further C-C bond formation [56][57][58][59]. MnCl 2 .4H 2 O was also supported on montmorillonite K-10, and used in the catalytic synthesis of benzaldehyde derivatives, by the H 2 O 2 -mediated oxidation of the corresponding alcohols [60].…”
Section: Resultsmentioning
confidence: 99%
“…Zinc oxide was submitted to trace metal analysis by inductively coupled plasma mass spectrometry (ICP‐MS) to exclude other elements known to perform alcohol dehydrogenation . Fortunately, none of these metals were observed beyond their detection limits of typically 1 ppm and the transformation is therefore not believed to be catalyzed by trace metal residues in zinc oxide.…”
Section: Resultsmentioning
confidence: 99%